Doing Science Differently: A Framework for Assessing the Careers of Qualitative Scholars in the Health Sciences. Issue 1 (3rd May 2019) - Webster, Fiona; Gastaldo, Denise; Durant, Steve; Eakin, Joan; Gladstone, Brenda; Parsons, Janet; Peter, Elizabeth; Shaw, James
Hiring and promotion of qualitative researchers in the health sciences, in Canada and internationally, is impacted by the prestige of quantification as the ultimate measure of scientific quality in current academic and health-care settings. This is further exacerbated by neoliberal notions of productivity, which offer very limited forms of assessment for different ways of producing knowledge or doing science differently . While qualitative researchers share the effects of the politics of productivity and corporate university policies with other academics, we argue that they are disadvantaged by the combination of the latent biomedical conservatism that characterizes the health sciences in Canada with the lack of frameworks to acknowledge and properly assess alternative forms of interdisciplinary scholarship. In our experience, it is challenging for qualitative researchers to advance in Canadian health sciences faculties. In light of this, we propose a framework for evaluating their scholarly work. We have structured this article in three sections: (a) to characterize the academic landscape in which qualitative health scholars find themselves when housed in Canadian faculties of medicine and their schools of health sciences, (b) to report on an organizational scan we undertook in order to understand current practices of evaluating scholarly productivity at these institutions, and (c) to propose a set of criteria that could more appropriately evaluate the contributions made by qualitative researchers working in the health sciences.